Dipeptidyl peptidase 4 (DPP4) inhibitor and outcome from coronavirus disease 2019 (COVID-19) in diabetic patients: a systematic review, meta-analysis, and meta-regression - Hariyanto, Timotius Ivan (J Diabetes Metab Disord, 2021)
BACKGROUND: One of the drugs which is commonly used in diabetic patients is Dipeptidyl Peptidase-4 (DPP-4) inhibitor. Currently, the association between DPP-4 inhibitor and coronavirus disease 2019 (COVID-19) outcome is not yet established. This study aims to analyze the potential association between DPP-4 inhibitor and the composite poor outcome of COVID-19. METHODS: We systematically searched the PubMed and Europe PMC database using specific keywords related to our aims until November 29th, 2020. All articles published on COVID-19 and DPP-4 inhibitor were retrieved. Statistical analysis was done using Review Manager 5.4 and Comprehensive Meta-Analysis version 3 software. RESULTS: Our pooled analysis showed that DPP-4 inhibitor use was not associated with composite poor outcomes of COVID-19 [OR 1.09 (95% CI 0.93–1.28), p = 0.29, I(2) = 0%, random-effect modelling], and its subgroup which comprised of severe COVID-19 [OR 1.07 (95% CI 0.87–1.31), p = 0.54, I(2) = 0%, random-effect modelling], and mortality [OR 1.14 (95% CI 0.87–1.51), p = 0.35, I(2) = 8%, random-effect modelling]. Meta-regression showed that the association was not influenced by age (p = 0.663), hypertension (p = 0.454), and admission blood glucose (p = 0.310). Subgroup analysis showed that the association was weaker in East Asian populations (OR 1.02) compared to European populations (OR 1.11). CONCLUSION: DPP-4 inhibitor in diabetic patients did not alter the outcomes from COVID-19. Our study suggest that the use of DPP-4 inhibitor in COVID-19 patients with diabetes may still be continued according to the patients’ need. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s40200-021-00777-4.